Dynamics of Organisational Capability of Japanese Construction Firm towards Open and Service Innovation through PPP/PFI arrangement - Taeko Suehiro; Kumiko Miyazaki (STI Policy and Management Journal, 2020)
This study examined the influence of Public–Private Partnership (PPP) — or, more specifically, Private Finance Initiative (PFI) — arrangements in relation to open and service innovation in construction firms in Japan. The expectation of the PPP/PFI procurement arrangement is that Japanese construction firms will provide a broader range of services (service innovation) through expanded cooperation with various other firms (open innovation) compared to the conventional procurement scheme.Our in-depth case study of a Japanese construction company shows the dynamics of project-based firms' capability accumulation through a PPP/PFI arrangement. The study identified a model of capability development for construction firms towards service and open innovation. It consists of three organisational capabilities: technological capabilities, project capabilities and collaborative capabilities. The model can be seen as an ideal approach for understanding and comparing cases of long-term capability accumulation of project-based firms, especially regarding providing services that meet the public's needs. Keywords: Public–Private Partnership (PPP); Private Finance Initiative (PFI); Project Capability, Open innovation; Service innovation; Construction firm